PENGARUH NILAI TUKAR, JUMLAH UANG BEREDAR, SUKU BUNGA TERHADAP INDEKS HARGA SAHAM SYARIAH SELAMA COVID-19 - Wijaya, Yusuf; Hariyani, Happy Febrina (Journal of Financial Economics & Investment, 2022)
The capital market has an important role in the economy in a country where the capital market also functions as funding for a company or business which is a means for the public to invest. This study aims to determine the effect of the exchange rate, money supply, interest rate on the Islamic stock price index during covid-19. The type of data used in this research is secondary data in the form of time series over a period of three years and eight months and sourced from Bank Indonesia, the Central Statistics Agency, and the Financial Services Authority which is take in monthly form. The analytical method used in this study uses multiple linier regression analysis. The results of this study are the exchange rate has a significant negative effect on the sharia stock price index, the money supply has a positive effect on the sharia stock price index, and interest rates have a positive effect on the sharia stock index.